AHMAD AMIN: KRITIK DAN PEMIKIRANNYA TENTANG HADIS - Nurmahni Nurmahni (The Pontianak State Institute of Islamic Studies, 2011)
Ahmad Amin was a modern muslim scholar that produced critical works in the field of Islamic thought, including critical thinking of Hadith.His critical thinking can be found in his most famous book entitled